Interaction and potential mechanisms between atorvastatin and voriconazole, agents used to treat dyslipidemia and fungal infections - Xun, Tianrong; Rong, Yan; Lv, Bin; Tian, Jinfei; Zhang, Qing; Yang, Xixiao (Frontiers in Pharmacology, 2023)
Purpose: Voriconazole (VOR) is combined with atorvastatin (ATO) to treat fungal infections in patients with dyslipidemia in clinical practice. However, the pharmacokinetic interactions and potential mechanisms between them are unknown. Therefore, this study aimed to investigate the pharmacokinetic interactions and potential mechanisms between ATO and VOR. Patients and methods: We collected plasma samples from three patients using ATO and VOR. Rats were administered either VOR or normal saline for 6 days, followed by a single dose of 2 mg/kg ATO, and then plasma samples were collected at different time points. The incubation models of human liver microsomes or HepG2 cells were constructed in vitro. A high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) system was developed to determine the concentration of ATO, 2-hydroxy-ATO, 4-hydroxy-ATO, and VOR. Results: In patients, VOR significantly reduced the metabolism of ATO and slowed the formation of 2-hydroxy- and 4-hydroxy-ATO. In rats pretreated with orally administered VOR for 6 days or normal saline given a single dose of 2 mg/kg ATO administered orally on Day 6, the t1/2 of ATO was significantly prolonged from 3.61 to 6.43 h, and the area under the concentration-time curve (AUC0–24h) values of ATO increased from 53.86 to 176.84 h μg.L−1. However, the pharmacokinetic parameters of VOR (20 mg/kg) with or without pretreatment with ATO (2 mg/kg) only slightly changed. In vitro studies indicated that VOR inhibited the metabolism of ATO and testosterone, and the IC50 values were 45.94 and 49.81 μM. However, no significant change in transporter behaviors of ATO was observed when VOR or transporter inhibitors were co-administered. Conclusion: Our study demonstrated that VOR has significant interactions with ATO, probably due to VOR’s inhibition of the CYP3A4-mediated metabolism of ATO. Based on the clinical cases and potential interactions, the basic data obtained in our study are expected to help adjust the dose of ATO and promote the design of rational dosage regimens for pharmacotherapy for fungal infections in patients with dyslipidemia.